State University of Land Use Planning - a driver of ecological development of small regions in the conditions of Covid-19 - Yuliya, Yurova; Vera, Shirokova; Roy, Shirokov; Pavel, Lepekhin; Alla, Khutorova (Journal of Sustainability Perspectives, 2022)
Responding to global global challenges and sustainable development goals, the State University of Land Use Planning (LUP) is trying to modernize its scientific, educational and economic activities and introduce the best available technologies in the field of rational nature management. The University pursues an environmental policy, which should become a guarantor of sustainable environmentally oriented development of small regions in accordance with the SDG.Since 2018, LUP has been actively participating in events organized by the IU Green Metric community. The use of the "green" campus practices offered by IU Green Metric for an educational organization contributes to the dissemination of a culture of sustainable development in relation to all stakeholders. The significance of the project is connected with the need to strengthen the practical elements of training environmental specialists; assessment of the anthropogenic load on the unique campus territory under the influence of intensive development of the district's infrastructure; the need to improve the general ecological culture of the population, as well as to ensure the competitiveness of Russian universities.The paper shows the features of the implementation of measures related to the environmentally sustainable development of small regions within the framework of educational field and production practices in the conditions of COVID-19, the experience of conducting a comprehensive geoecological assessment of the Osetr river basin in the period 2015-2021, agroecological assessment with subsequent analysis of the state of agroecosystems based on the results of systematic regular observations for the rational use and protection of landscapes on the territory of the SEB "Gornoye", the need for the development of ecological educational tourism is noted in connection with the active development of the tourism industry, which is accompanied by an increase in the anthropogenic load on the environment. Keyword: geoecology, sustainable ecological development, field practices, ecological tourism, recreation